Recommended Initial Antimicrobial Therapy for Emphysematous Pyelonephritis: 51 Cases and 14-Year-Experience of a Tertiary Referral Center. Issue 21 (May 2016) - Lu, Yu-Chuan; Hong, Jian-Hua; Chiang, Bing-Juin; Pong, Yuan-Hung; Hsueh, Po-Ren; Huang, Chao-Yuan; Pu, Yeong-Shiau
Abstract : Abstract: The aim of this study was to investigate the profiles of pathogens and patterns of antibiotic resistance of emphysematous pyelonephritis (EPN), offering recommendations for initial antibiotic treatment. Between January, 2001, and November, 2014, demographic data, presenting clinical features, management strategies, and treatment outcomes of 51 patients with EPN were retrospectively reviewed, analyzing microbiological characteristics of causative pathogens and patterns of antibiotic resistance. Overall survival rate was 90.2% (46/51). Pathogens isolated most frequently were Escherichia coli (49.0%), Klebsiella pneumoniae (19.6%), and Proteus mirabilis (17.7%). Approximately 24% of E coli isolates and 22% K pneumoniae isolates were resistant to fluoroquinolones. Improper empiric antibiotic use ( P  = 0.02) and third-generation cephalosporin-resistant pathogens (G3CRP) ( P  = 0.01) were significantly more common in cases of patient fatality. Prior hospitalization and antibiotic use within past year ( P  = 0.03), need for emergency hemodialysis ( P  = 0.03), and development of disseminated intravascular coagulation (DIC) ( P  = 0.03) were factors correlating significantly with microbial resistance to third-generation cephalosporins. The area under the receiver operating characteristic curve was 0.91. The cut-off point determined by the maximum Youden index for 2 of these 3 factors yielded a sensitivity of 0.8 and specificity of 0.93. Third-generation cephalosporins are recommended as initial treatment of EPN. In patients with histories of prior hospitalization and antibiotic use and in those needing emergency hemodialysis or developing DIC, carbapenem is the empiric antibiotic of choice. Patients presenting with 2 or more factors carry the highest risk of G3CRP involvement. Fluoroquinolone and gentamicin should be avoided.